Synthesis, characterization and in-vitro study of hydroxyapatite, silver substituted hydroxyapatite and iron substituted hydroxyapatite for bone tissue engineering applications - Sonia Sharma; Parveen Goyal (Results in Chemistry)
Calcium phosphate-based biomaterials resemble the inorganic composition of bone, they have attracted attention for bone tissue engineering applications. These compositions tend to develop an interface with the target bone because they are bioactive, bioresorbable, and biocompatible. Hydroxyapatite (HA) has gained importance among calcium phosphates because of its orthopaedic and dental applications.The ability of hydroxyapatite to exchange ions in the lattice framework allows the substitution of different ions to improve the resorbability of the ceramics. This study used a water-based sol-gel approach to create nano-dimensional HA and substituted (with ions Ag+ and Fe2+) nanopowders. X-ray florescence spectroscopy (XRF) was used for the compositional study, and X-ray diffraction (XRD) was used to ascertain the lattice parameters, phase transitions, purity, and crystallinity. FTIR, Fourier Transform Infrared Spectroscopy, was used to identify the functional groups. In-vitro study was performed by immersing the nanopowders at 37 °C in SBF for 30 days. The crystallinity of the nanopowders increased as the calcination temperature increased from 800 °C to 1200 °C. The crystallinnity of the calcined HA, Ag-HA, and Fe-HA, was found to be in the range of 85–98 %, 77–89 %, and 83–89 %, respectively. The mean crystallite size of the as-synthesized HA, Ag-HA, and Fe-HA nanopowders were 17.23 Ao, 9.155 Ao, and 9.4363 Ao, respectively. The mean crystallite sizes of the nanopowders increased with increase in the calcination.